Analisis Rasio Pada Instagram Untuk Penelitian Kualitatif Menggunakan Metode Ekploratif - Permana, I Putu hendika (Jurnal Sistem Informasi dan Komputer Terapan Indonesia (JSIKTI), 2021)
Information and Communication Technology is currently growing rapidly so that it can make it easier for everyone to exchange information with others through social media. One of the social media that currently has a big influence is Instagram. This study aims to find the ratios found on social media Instagram. These ratios can later be used to perform analyzes that can be measured mathematically. The research method used is exploratory to find the variables contained in Instagram. These variables will be juxtaposed to be tested for their relevance to find the relevant ratios used to assess the performance of an Instagram account. The results of this Instagram social media research show that 14 ratios can be used to assess, measure, and compare the credibility of an Instagram account. The discovery of this ratio implies that further researchers can conduct quantitative research in measuring, assessing, and comparing accounts contained on Instagram.